NATURAL AND MAN-CAUSED FACTORS OF CENOMANIAN-CALLOVIAN GROUNDWATER COMPLEX CHEMICAL COMPOSITION FORMATION WITHIN URBAN AGGLOMERATION OF KYIV - Koshliakova, T.; Dolin, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Purpose. Determination of patterns of cenomanian-callovian groundwater complex chemical composition formation in Kyiv due to man-caused influence. Methodology. During the study, the following approaches were used: mathematical methods of hydrogeological data processing (normalization of groundwater chemical composition parameters, determination of mineral substances export man-caused flow capacity, regression analysis and exponential trending). For graphs construction Excel and Statistica programs were used. Findings. The regularities of cenomanian-callovian groundwater complex chemical composition changes in Kyiv during the 1980s–2010s, based on primary parameters, were investigated. Correlation between changes of study groundwater complex chemical composition normalized parameters and water intake intensity was analyzed. Regular increase of mineral substances content with water intake decrease was revealed. The capacity of man-caused flow of mineral substances export from study groundwater complex was estimated. It was determined, that the dynamics of mineral substances man-caused flow parameters with high correlation coincides with the dynamics of power generation in Ukraine. Temporal patterns of water quality parameters changes were defined. The rate constant of mineral substances man-caused flow parameters changes during the1980s–2010s was calculated. Originality. It was defined that cenomanian-callovian groundwater complex quality, used as potable water source for Kyiv population, is extensively determined by man-caused factors, such as industrial production and water intake intensity. Significant negative correlation (Kcor 0,6 – -0,85) between water quality normalized parameters value, mineral substances export value, water intake intensity and industrial production output (estimated by power generation in Ukraine) was revealed. Practical value. The resulting research exponential trends of dynamics of mineral substances man-caused flow parameters, especially calculated rate constants of their changes during the 1980s–2010s, can serve as an instrument of groundwater chemical composition prediction in conditions of intensive water intake. Principles of application of exponential regression together with correlation analysis procedures allow to reveal both groundwater chemical composition quality parameters connection with man-caused factors and temporal trends of their changes, and can be successfully applied to urban areas.
Keywords: groundwater; water intake; man-caused influence; regression; trend; rate constant